Manajemen Pendidikan Islam dalam Membentuk Karakter Siswa di Madrasah Ibtidaiyah - Saidur Ridlo (MODELING: Jurnal Program Studi PGMI, 2021)
Education has an important and central role in the development of human potential, including mental potential. Through education, it is hoped that a transformation will occur that can develop positive characters, and change character from bad to good. National education gives a mandate to schools/madrasas as formal educational institutions to organize a learning process that can enable the development of a social culture that gives birth to the character and civilization of the nation. The purpose of this study is to explain the management of Islamic education in shaping the character of students at Madrasah Ibtidaiyah. The method in this study uses a qualitative method with the type of descriptive analytic research. The results of this study that in shaping the character of students need Islamic education management so that character education planning is needed, character education organization, character education implementation, and character education supervision is needed. Documentary character education is integrated into the curriculum. In the development of character education, it is socialized to school members such as teachers, employees, and students as well as to parents and the community. As well as character values ​​are integrated into learning planning.